SIKAP DAN PERILAKU WIRAUSAHAWAN - Suharyono Suharyono (Jurnal Ilmu dan Budaya, 2017)
Economic development of a country restx heavily on the presence of entrepreneurs who are competent and qualified to run business. How should a businessman be described and developed? The paper tries to give a comprehensive decription of entrepreneurs including the necessity to have several qualificatios of a good entrepreneur.  At the end of the paper suggestions are made on how the knowledge , skills and attitude are implemented in practice.